(untitled) (Anclajes, 2020)
The articles in this issue focus on the ways in which gender violence impacts its own contexts and communities materially, symbolically, and subjectively. The texts address femicides-feminicides, the exploitation and racialization of bodies within the framework of “gore capitalism” as understood by Sayak Valencia, as well as the violence inflicted on bodies within the border-related contexts of migration and deportation.